A spatio-temporal dataset on food flows for four West African cities - Karg, Hanna Laura; Akoto-Danso, Edmund Kyei; Amprako, Louis; Drechsel, Pay; Nyarko, George; Lompo, Désiré Jean-Pascal; Ndzerem, Stephen; Sidibe, Seydou; Hoschek, Mark; Buerkert, Andreas (2023)
Abstract: Gaining insight into the food sourcing practices of cities is important to understand their resilience to climate change, economic crisis, as well as pandemics affecting food supply and security. To fill existing knowledge gaps in this area food flow data were collected in four West African cities - Bamako (Mali), Bamenda (Cameroon), Ouagadougou (Burkina Faso), and Tamale (Ghana). The data cover, depending on the city, road, rail, boat, and air traffic. Surveys were conducted for one week on average during the peak harvest, lean, and rainy seasons, resulting in a dataset of over 100,000 entries for 46 unprocessed food commodities. The data collected includes information on the key types of transportation used, quantity, source, and destination of the food flows. The data were used to delineate urban foodsheds and to identify city-specific factors constraining rural-urban linkages. The data can also be employed to inform academic and policy discussions on urban food system sustainability, to validate other datasets, and to plan humanitarian aid and food security interventions